Nursing assistance to the patient victim of cranioencephalic traumatism (Research, Society and Development, 2021)
This study aims to carry out an integrative review of nursing care for patients who are victims of traumatic brain injury. This is an integrative literature review, the search took place in the Virtual Health Library (VHL), with the aid of the Latin American and Caribbean Literature in Health Sciences (LILACS) databases, Nursing Databases (BEDENF), Virtual Scientific Electronic Library Online (SciELO) and PUBMED. The articles were collected in the period of June 2021. The descriptors were used: Craniocerebral trauma, Nursing care and Nursing. After analyzing the articles found, 10 studies were selected to compose the present work. The study points out that the nurse has a fundamental role in the care offered to victims of traumatic brain injury, it’s necessary for him to be able to obtain a brief history of the patient, perform the physical examination, and carry out immediate treatment, worrying about the maintenance of life. It must combine its theoretical foundation with leadership capacity, initiative and care and teaching skills. he needs to be quick thinking, as he is responsible for coordinating a nursing team, being a vital and integral part of the emergency team.